WORKSHOP REPORT ON THE ISLAMIZATION OF KNOWLEDGE (American Journal of Islam and Society, 1997)
The workshop on the Islamization of knowledge, organized by theKulliyyah of Islamic Revealed Knowledge and Human Sciences, washeld at Regency Hotel, Port Dickson, Negeri Sembilan, Malaysia, fromJune 7-11, 1996. Workshops and seminars of this sort usually revolvearound the nature, characteristics, and rationale for the Islamization ofknowledge. This workshop, however, was different in that it dealt withthe question of methodology. Given that Islamization is an intellectualand methodological outlook, the workshop’s emphasis on methodologyis justified and well placed.Clearly, the workshop was not for the uninitiated or for new recruits.It was meant for those who have been associated with the movement forthe Islamization of knowledge and especially for those who have thepotential to make some contribution toward its realization. Clearly, thelist of participants indicates that the organizers selected those who areimbued with a spirit of selflessness and zeal to work for the sake of Islamto uplift the Ummah’s image intellectually and otherwise.The workshop,as briefed by Louay Safi, was an occasion to scrutinize in minute detailthe parameters of the Islamization of knowledge, to critically appreciatethe contributions made by the leading luminaries, and to grapple seriouslywith questions of methodology ...